Analysis on predistortion algorithm for improving adjacent channel leakage ratio of radio over fiber systems. Issue 4 (24th December 2019) - Yang, Bo; He, Hongxia; Yang, Shuna; Ou, Jun; Zhai, Yanrong; Chi, Hao
Abstract: Nonlinear distortion introduced by optoelectronic components imposes serious limitations on the performance of radio over fiber (RoF) systems, such as dynamic range and adjacent channel leakage ratio (ACLR). In this article, we focus on the impact of digital predistortion (DPD) on the ACLR improvement in a wideband RoF system with multiple carriers. Three key factors, that is, the order of DPD algorithm, the initial phases of carriers, and the processing bandwidth of the predistortion module, are all taken into account in investigating the influence of predistortion on the ACLR performance of RoF systems. A preliminary experiment verifies the effectiveness of predistortion technique for improving the ACLR performance. Quantitative simulation results demonstrate that with the increase in the order of DPD algorithm, the ACLR performance can be significantly improved while the phase randomness within 10 carriers leads to an ACLR fluctuation up to 5 dB. The dependence of the ACLR improvement on the processing bandwidth of the predistortion module, which is very important in practical application, has also been quantitatively studied.